Bolstering the Case for Lobectomy in Stages I, II, and IIIA Small-Cell Lung Cancer Using the National Cancer Data Base. Issue 2 (February 2015) - Combs, Susan E.; Hancock, Jacquelyn G.; Boffa, Daniel J.; Decker, Roy H.; Detterbeck, Frank C.; Kim, Anthony W.
<x xml:space="preserve">Abstract</x> Introduction: Current therapy for small-cell lung cancer (SCLC) relies on chemoradiation therapy, and the role of primary surgical resection in these patients remains controversial. A minority of SCLC patients present without metastatic disease and are candidates for surgery. This study investigates the role of surgical resection in select patients with SCLC, using a national cohort of approximately 2500 resected patients. Methods: A retrospective study of SCLC patients in the National Cancer Data Base (NCDB) was performed where patients were grouped for comparison by stage and treatment regimen. Survival was estimated by Kaplan–Meier methods and multivariate comparisons using Cox regression. Results: Of 28, 621 cases of potentially resectable SCLC, 2476 patients (9%) underwent surgery of the primary site with curative intent. Five-year overall survival for patients after resection was 51%, 25%, and 18% for clinical stages I, II, and IIIA, respectively. Addition of surgery to chemotherapy was associated with decreased likelihood of death (hazard ratio: 0.57, 95% confidence interval: 0.47–0.68), independent of age, stage, and comorbidity score. Lobectomy was associated with a 5-year overall survival of 40% compared with 21% and 22% for sublobar resection and pneumonectomy, respectively. Hazard ratio for death after sublobar resections compared with lobectomy was 1.38 (95% confidence interval: 1.12–1.71). Conclusions: Patients with stages I, II, and III SCLC, who underwent surgical resection as part of initial treatment with chemotherapy had respectable OS. These data may warrant prospective studies of including surgery in the multimodality treatment of SCLC in specific circumstances.